Deviation sexsual LGBT-Z: preelemanary research from counseling perspective - Alizamar Alizamar (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2019)
The rise of coverage of LGBT-Z sexual deviations have led to a polemic in the midst of society. LGBT-Z sexual deviation if not intervened will have an impact on the health, education, social in the community. This condition is caused by various factors, including ignorance of parents, genetics, religion. This phenomenon tends to be even greater in millennial. This type of research is library research that focuses on LGBT-Z sexual deviation behavior. One professional who is considered capable as a solution to the problems that occur in the community is a counselor. Counselors can provide guidance and counseling services that focus on LGBT-Z sexual deviation behavior such as individual counseling, psychological approaches that are needed. It is hoped that the psychological assistance provided by individual counselors will be able to avoid LGBT-Z sexual deviation behavior.